“Andar com fé eu vou!” Entre transições e tradições: um pouso cartográfico sobre as trajetórias dos jovens de terreiro em Bonfim de Feira - Rodrigues, Milena Santos (2015)
This research focuses on understanding the life trajectories of young people linked to the african-Brazilian religions of the Bonfim de Feira district from crossings social, cultural and religious that circumscribe their ways of life. The work has outlined in order to broaden the discussions on the topic of youth, enhancing the look and the voice of young people in approaching with their own social experiences. Thus, the theoretical categories were addressed: youths and trajectories concomitantly with the concepts of temporality and transitions. the theoretical categories religiosity and belonging were also discussed, seeking to evidences how these two dimensions are articulated in the configuration of hybrid identities. The methodology adopted was of qualitative nature and the cartographic method was chosen as research strategy, focusing on the interactions with the place (Bonfim de Feira) and the subjects, in the apprehension of intersubjective processes between the researcher and the researched. The analysis of narrative interviews were organized so as to highlight the singularities present in each trajectory of young people interviewed as well as show discussions about the transition from the common aspects of their careers such as school, work, employability, community experiences, cultural and religiosity. Thus, this research has allowed us to understand that young people are inserted in a context marked by strong cultural and religious tradition, that offer to them anchors in preparing for the future. They Experience tensions in the relationship between school and work, migrate and stay, while seeking to negotiate other forms of sociability as well as reinventing forms of belonging and to give continuing to the traditions of the place.